2016
DOI: 10.1111/jace.14313
|View full text |Cite
|
Sign up to set email alerts
|

Conduction Mechanisms in BaTiO3–Bi(Zn1/2Ti1/2)O3 Ceramics

Abstract: Polycrystalline BaTiO3–Bi(Zn1/2Ti1/2)O3 (BT–BZT) ceramics have superior dielectric properties for high‐temperature and high‐energy density applications as compared to the existing materials. While it has been shown that the addition of BZT to BT leads to an improvement in resistivity by two orders of magnitude, in this study impedance spectroscopy is used to demonstrate a novel change in conduction mechanism. While nominally undoped BT exhibits extrinsic‐like p‐type conduction, it is reported that BT–BZT ceram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 40 publications
5
26
0
Order By: Relevance
“…A decrease in resistivity is observed in atmosphere of lower oxygen partial pressure (Nitrogen), which is an indication of n ‐type behavior. The n ‐type character in these samples may be due to addition of BMT, which may act like donor as reported previously for BZT added BT …”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…A decrease in resistivity is observed in atmosphere of lower oxygen partial pressure (Nitrogen), which is an indication of n ‐type behavior. The n ‐type character in these samples may be due to addition of BMT, which may act like donor as reported previously for BZT added BT …”
Section: Resultssupporting
confidence: 54%
“…The second end‐member of the composition BMT contains bismuth and mostly these compounds also exhibit extrinsic conduction due to the evaporation of bismuth during high‐temperature sintering. The type of charge carrier can be identified by measuring impedance in atmospheres of different oxygen partial pressure . Oxygen incorporation leads to creation of holes according to the Equation .…”
Section: Resultsmentioning
confidence: 99%
“…Several Bi M O 3 compounds, for example, (Bi 1/2 Li 1/2 )TiO 3 , Bi(Mg 2/3 Nb 1/3 )O 3 , Bi(Mg 1/2 Ti 1/2 )O 3 , Bi(Zn 2/3 Nb 1/3 )O 3 , Bi(Zn,Sc,Ti)O 3 have been shown to exhibit the same effect on the electrical properties when added to BaTiO 3 . Studies to determine the type of charge carrier in these solid solutions are scarce, however, some of them have been shown to exhibit a simultaneous p‐type to n‐type transition of majority charge carriers, along with resistivity enhancement . This article primarily focuses on BT‐BZT ceramics with an aim of understanding the transport mechanisms and to establish the defect chemistry for the BT‐Bi M O 3 class of materials in general.…”
Section: Resultsmentioning
confidence: 99%
“…In separate reports on macroscopic transport properties, it was shown that on forming solid solutions with small amounts of Bi M O 3 to BT, their insulation properties improve by multiple orders of magnitude. There is also a corresponding transition from p‐type behavior for BT towards n‐type for BT‐Bi M O 3 ceramics without any deliberate donor doping, indicating a drastic change in underlying defect equilibrium conditions . A thorough study of the complex defect mechanisms in BT‐Bi M O 3 has been performed in this article, which intends to explain the observed change in transport properties on adding Bi‐perovskites to BT.…”
Section: Introductionmentioning
confidence: 96%
“…The undoped BT used in this study is characterized by a defect-dominated p-type conduction mechanism, as reported in a previous paper. 45 In BT, the p-type behavior is commonly attributed to frozen-in cation vacancies formed during high temperature processing and low valence acceptor impurities associated with starting reagent oxides. [46][47][48] These vacancies and acceptors can be compensated by oxygen vacancies, which can in turn give rise to p-type behavior at high oxygen partial pressures as per following defect reaction:…”
Section: Bb-bt Ceramicsmentioning
confidence: 99%